2022
DOI: 10.1002/ldr.4456
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of grass planting density and components on overland flow hydraulics and soil loss

Abstract: Although abundant studies have confirmed the positive effect of vegetation on runoff and soil erosion reduction, few studies have clarified the effects of planting density and its components (aboveground parts and roots) on slope runoff and soil erosion mechanisms. A series of field experimental plots were constructed on two slopes (3 , 6 ), including a bare land plot as the control, three grassed plots with three grass (Agropyron cristatum) planting densities of 20 cm  20 cm, 15 cm  15 cm, and 10 cm  10 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…However, considering other factors beyond flow depth, such as soil composition, vegetation structure, or slope characteristics (Li et al, 2019; Pan, Ma, Wainwright, & Shangguan, 2016b; Xiao et al, 2017), may reveal their potential to overshadow the effects of clipping intensity. For instance, Fu et al (2022) suggested that the roots were the main contributor to the reduction in overland flow shear capacity, accounting for 89.7% of the total reduction. The presence of litter cover in grasslands creates a stable near‐surface layer, which is disrupted when aboveground components are removed through clipping treatments, resulting in a sparse density of stem elements.…”
Section: Discussionmentioning
confidence: 99%
“…However, considering other factors beyond flow depth, such as soil composition, vegetation structure, or slope characteristics (Li et al, 2019; Pan, Ma, Wainwright, & Shangguan, 2016b; Xiao et al, 2017), may reveal their potential to overshadow the effects of clipping intensity. For instance, Fu et al (2022) suggested that the roots were the main contributor to the reduction in overland flow shear capacity, accounting for 89.7% of the total reduction. The presence of litter cover in grasslands creates a stable near‐surface layer, which is disrupted when aboveground components are removed through clipping treatments, resulting in a sparse density of stem elements.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some research results have shown that soil erodibility is closely related to environmental factors (soil physical and chemical characteristics, vegetation cover and root characteristics, cover type, topography, and geomorphology) [ 23 , 24 , 25 , 26 ]. First, the enhancement of soil anti-erodibility is mainly attributed to the improvement in soil structure, soil shear strength, and soil aggregate stability [ 27 , 28 , 29 ]. Bulk density (BD) and soil texture, among others, have significant effects on aggregate soil stability, infiltration, and soil shear strength [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since 1999, in response to soil erosion control and ecological restoration, the “Grain for Green” project has been implemented on the Loess Plateau, which has considerably improved the vegetation cover and ecological environment (Cao et al, 2020; Wu et al, 2019; Zhang et al, 2021). Ground cover comprising grass, shrubs, trees, and crops is closely related to the reduction in soil erosion (Fu et al, 2023; Kervrodan et al, 2020; Liu, Liu, et al, 2020). Herbaceous plants have a higher level of efficacy in reducing soil erosion than shrubs and trees (De Baets et al, 2007; Duan et al, 2019; Lin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The primary anti‐erosion mechanism of herbaceous plants is predominantly achieved by the increase in aboveground vegetation biomass and root density (Cao et al, 2015; Casermeiro et al, 2004; De Baets et al, 2007). Given the difference in the anti‐erosion ability between the aboveground canopy and the root system of herbaceous plants, the contribution rate of different grass components to soil loss reduction may be different (Fu et al, 2023; Li & Pan, 2018; Ma et al, 2013; Pan et al, 2010). Aboveground grass vegetation components have been found to be more effective in reducing the overland flow rate and velocity (Li & Pan, 2018; Ma et al, 2013).…”
Section: Introductionmentioning
confidence: 99%